VASCULAR REMODELING IN PATIENTS WHO ARE IN PROGRAM HEMODIALYSIS - B. T. Daminov; B. M. Mirzaeva (Евразийский Кардиологический Журнал)
Chronic kidney disease is associated with the accumulation in the blood of the so-called medium molecules, in particular parathyroid hormone, and the development of secondary hyperparathyroidism with a tendency to extracellular calcification. The most vulnerable organ in relation to calcification is the vascular wall. Objective. To study the characteristics of remodeling of the vascular wall in patients with chronic kidney disease (CKD) undergoing treatment with programmed hemodialysis.